Comparison of rehabilitation interventions in nonoperatively treated distal radius fractures: a randomized controlled trial of effectiveness. (1st June 2021) - Coughlin, Tim; Norrish, Alan R.; Scammell, Brigitte E.; Matthews, Paul A.; Nightingale, Jessica; Ollivere, Ben J.
Abstract : Aims: Following cast removal for nonoperatively treated distal radius fractures, rehabilitation facilitated by advice leaflet and advice video were compared to a course of face-to-face therapy. Methods: Adults with an isolated, nonoperatively treated distal radius fracture were included at six weeks post-cast removal. Participants were randomized to delivery of rehabilitation interventions in one of three ways: an advice leaflet; an advice video; or face-to-face therapy session(s). The primary outcome measure was the Disabilities of the Arm, Shoulder and Hand (DASH) score at six weeks post intervention and secondary outcome measures included DASH at one year, DASH work subscale, grip strength, and range of motion at six weeks and one year. Results: A total of 116 (97%) of 120 enrolled participants commenced treatment. Of those, 21 were lost to follow-up, resulting in 30 participants in the advice leaflet, 32 in the advice video, and 33 face-to-face therapy arms, respectively at six weeks of follow-up. There was no significant difference between the treatment groups in the DASH at six weeks (advice leaflet vs face-to-face therapy, p = 0.69; advice video vs face-to-face therapy, p = 0.56; advice leaflet vs advice video, p = 0.37; advice leaflet vs advice video vs face-to-face therapy, p = 0.63). At six weeks, there were no differences in any secondary outcome measures except for the DASH work subscale, where face-to-face therapy conferred benefit over advice leaflet (p = 0.01). Conclusion: Following cast removal for nonoperatively treated distal radius fractures, offering an advice leaflet or advice video for rehabilitation gives equivalent patient-reported outcomes to a course of face-to-face therapy.